Can principles of the Chronic Care Model be used to improve care of the older person in the acute care sector? - Hickman, L.; Rolley, John; Davidson, Patricia (Royal College of Nursing Australia, 2010)
Background: There is increasing evidence that hospitals are failing to meet the needs of older people. As a consequence acute care needs to be adapted to meet the needs of older people. Although initially developed for chronic conditions the Chronic Care Model (CCM) provides useful strategies for improving continuity and quality of care. Method/aim: This paper describes the elements of the CCM and discusses how a chronic care approach can improve models of care delivery for older persons in the acute care hospital settings. Discussion: The CCM provides a potentially useful approach to improve health care for older people in the acute care setting. Positive policy environments, interdisciplinary care collaboration, evidence-based practice, an emphasis on self-management strategies and empowered communities are essential elements for driving development of effective models of care. Conclusion: Models of care require a multifaceted collaborative approach for sustainability. Implementing elements of the CCM in developing models of acute care may improve patient outcomes and decrease unnecessary admissions to hospital for older people. Implications for practice: This paper provides suggestions for models of care to improve care of the older person in the acute care setting.